The Process of Changing Modern Traditions in the Uzbek Opera Theater - Rayetovich, Gafarov Ruslan (Researchparks Publishing, 2023)
During the years of independence the issues of development and strengthening the spiritual culture of the population are a priority of state importance. Recently, more and more attention has been paid to organizing and conducting scientific forums and conferences, international and republican contests. One of such heritage of national spiritual revival is the art of opera. In particular, the opera theater. Let us dwell on it in more detail. The article deals with the issues of Uzbek opera art. On the material of the analysis of the opera genre in the works of modern Uzbek composers the expressive means, aimed at educating the younger generation through the art of opera are identified.